RELATIONSHIP MARKETING, CUSTOMER SATISFACTION, CUSTOMER COMMITMENT DAN CUSTOMER LOYALTY (STUDI PADA SEBUAH BANK NASIONAL DI DENPASAR) - Budi Martini, Luh Kadek (Buletin Studi Ekonomi; Vol 18, No. 1,Februari 2013. (PP 1-84), 2013)
Various approaches to marketing strategy applied by the organization to maintain companies viability and customer loyalty. This condition is the hope for every organization, considering the role of consumers as the company's assets can not be underestimated. Relationship marketing concept as a new breakthrough in the world of marketing gives new faces to build sustainable customer loyalty. With proper relationship marketing concept application, will be realized that the commit behavior of consumers to companies have implications on customer loyalty. The results showed that the association relationship marketing has positive and significantly implications for customer loyalty and customer commitment. While the implications of the formation of a commitment to loyalty also showed a positive and significant relationship.
Keywords: relationship marketing, customer satisfaction, customer commitment, customer loyalty